Food Security and the Right to Food in the European Union .......... 153 - Hałub-Kowalczyk, Olga (Fundamental Rights and Climate Change: Exploring New Perspectives and Corresponding Remedies, 2025)
In recent years the discussion on food security in the European Union (hereinafter the “EU” or “Union”) seems to have intensified and has begun to be one of the leading issues in the EU-agenda. The reason for it might be especially, i.a., the climate crisis. The EU food safety policy is based on the following pillars: food hygiene, animal and plant health, and contaminants and residues. Despite the urgent need to undertake actions towards the aforementioned directions, the new approach linking food security with access to food for each individual is needed. Moreover, this approach, based on the paradigm of food as a fundamental need, is not new in law. Already the 1948 Universal Declaration of Human Rights as well as the ICESCR relate to nutrition as a perquisite to enjoyment of other human rights. The same tendency was confirmed by the European Court of Human Rights (hereinafter the “ECtHR”), which stated that a lack of access to food can constitute a serious breach of Art. 3 of the ECHR. Meanwhile in the European Union law there is no legislation which classifies food as “public/common good” or “human right”. Therefore, the aim of this chapter is to verify how the process of recognition and implementation of the “right to food” in the EU progresses against the international standards.